Between Intimacy and Violence: Portrayals of Transgression in Donna Tartt’s The Secret History and Bret Easton Ellis’ American Psycho - Feki, Rahma (FOCUS: Papers in English Literary and Cultural Studies, 2025)
Dark academia has become a buzz word on social media platforms in recent years thanks to texts such as Donna Tartt’s The Secret History. Its significant rise in popularity was the result of many young readers discovering Tartt’s text and building an aesthetic around it that does not only include literary interest but extends to fashion as well. Dark academia primarily arose as a trendy literary subculture characterized by its fascination with a specific kind of intellectual elitism, one that is related to prestigious academic institutions. As readers are drawn to secluded campuses and dark gloomy libraries, the genre continues to sustain the allure surrounding mystery as transgressive acts unfold in these institutions’ halls. Historically, transgression in literature has been explored and discussed predominantly by male authors, with varying narratives centered around the violation of social and moral codes and, therefore, reveling in the aesthetics of aberration. Within academic settings, such as those depicted in The Secret History, the insular nature of elite educational institutions allows for the flourishing of stories about decaying morals because established systems of secrecy and exclusion provide a fertile ground for transgression to take place. That is why dark academia affords an apt framework for Donna Tartt to examine how transgressive acts can lure in readers enamored with enigmatic narratives situated in institutions that, on the surface, are said to uphold the highest standard of morality. This paper claims that The Secret History and American Psycho by Bret Easton Ellis, the most well-known American transgressive author with connections to Tartt, engage modes of transgression through distinct narrative approaches. By arguing that Tartt’s novel is a dark academia psychological thriller and Ellis’s as a horror-infused social satire, the article exposes how these authors investigated violence, intimacy, and moral boundaries in their own midst.